PEMANFAATAN SABUT KELAPA MELALUI METODE SLOW SAND FILTRATION UNTUK MEMENUHI KEBUTUHAN AIR BERSIH DI DESA TALANG TINGGI SELUMA - Abdul Rahman Singkam; Ananda Putri Gita Natasya; Fadjri Fil Ahli Hady; Nyimas Ajeng Ayu Meilani; Septia Noparis Fadhila; Anjaly Dewi Puspitasari; Mustika Elmi Dayana (Jurnal Penelitian dan Pengabdian Kepada Masyarakat UNSIQ, 2023)
The sources of clean water is very important for everyone to support their life needs. However, Talang Tinggi Village, Seluma Regency has poor water supply conditions, indicated by the physical condition of the water which smells, the color is brown, and has sediment. This condition is getting worse because the source of water will be mixed with soil and mud. Talang Tinggi village does not have PDAM access yet, so the need for clean water only relies on natural water sources, swamp water and well water. This community service aims to overcome the problem of water resources in Talang Tinggi Village, Seluma Regency, Bengkulu Province by utilizing coconut fiber waste, as a filter media in the Slow Sand Filtration method. The results of the activity showed that there was a very significant improvement in water quality. The water that was cloudy and smelled becomes clearer and odorless. The value of acidity (pH) of the water sample also increased from 6.05-7.38 to 6.5-9.0. These results indicate that coconut fiber, which has been considered as waste, can be used to an effective filter for cleaning water.